Embodiment in High-altitude Mountaineering: Sensing and Working with the Weather. (March 2019) - Allen-Collinson, Jacquelyn; Crust, Lee; Swann, Christian
In order to address sociological concerns with embodiment and learning, in this article we explore the 'weathering' body in a currently under-researched physical-cultural domain. Weather experiences, too, are under-explored in sociology, and here we examine in depth the lived experience of weather and, more specifically, 'weather work' and 'weather learning' in one of the most extreme and corporeally challenging environments on earth: high-altitude mountains. Drawing on a theoretical framework of phenomenological sociology, and an interview-based research project with 19 international, high-altitude mountaineers, we investigate weather as lived and experienced both corporeally and cognitively. We are particularly interested in conceptualizing and theorizing the ways in which embodied beings relate to the environment through different aspects of their being. The novel concepts of 'weather work' and 'weather learning', we argue, provide salient examples of the mind-body-world nexus at work, as an embodied practice and mode of thinking, strongly contoured by the physical culture of high-altitude mountaineering.